Inappropriate publication of trial results and potential for allegations of illegal share dealing. Issue 6885 (24th April 1993) - Freestone, D S; Mitchell, H
Abstract : There is increasing evidence of fraud in clinical research, and one aspect concerns trading in pharmaceutical company shares by people who may have confidential information about the results of clinical trials. Plainly this has implications for honest investigators, who may find themselves exposed to such allegations. In this paper Dr D S Freestone and Mr H Mitchell, QC, identify three interlinked issues which they think underlie the potential for these allegations. They are pressure for premature or inappropriate communication of research results; trading in pharmaceutical company shares by academic clinical investigators; and the possibility that clinical investigators might succumb to temptation. Dr Freestone and Mr Mitchell suggest that whenever possible results of clinical studies should be published in appropriate medical journals without prior public disclosure. This conflicts with Stock Exchange rules, which require that price sensitive information should be published at the earliest opportunity and preclude priority of publication in medical journals. Freestone and Mitchell believe that rarely rapid public disclosure is acceptable if it is to protect patients' interests but that it must not prejudice publication in the medical or scientific press. When rapid public disclosure is needed, they say, every attempt should be made to inform prescribers before patients. Dr Freestone and Mr Mitchell warn that academic clinical investigators who have access to unpublished price sensitive information about pharmaceutical companies whose shares they trade in will almost certainly be in breach of the Company Securities (Insider Dealing) Act 1985. Furthermore, disclosing such information to third parties, they say, exposes those people also to potential criminal liability. Freestone and Mitchell advise that when potential for allegations of conflict of interest exists clinical investigators should consider declaring their position to ethics committees and any sponsoring organisations.